2020
DOI: 10.46586/tches.v2020.i4.154-188
|View full text |Cite
|
Sign up to set email alerts
|

Improving the Performance of the Picnic Signature Scheme

Abstract: Picnic is a digital signature algorithm designed to provide security against attacks by quantum computers. The design uses only symmetric-key primitives, and is an efficient instantiation of the MPC-in-the-head paradigm. In this work, we explore the Picnic design in great detail. We investigate and benchmark different parameter choices and show that there exist better parameter choices than those in the current specification. We also present improvements to the MPC protocol that shorten signatures and reduce s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
10
0
2

Year Published

2021
2021
2022
2022

Publication Types

Select...
5
2

Relationship

1
6

Authors

Journals

citations
Cited by 28 publications
(17 citation statements)
references
References 8 publications
0
10
0
2
Order By: Relevance
“…We use our modified version of Reverie to implement post-quantum ring signatures. Our ring signatures, based on the postquantum signatures presented in [15,34,35], are the smallest known post-quantum ring signatures from symmetric key assumptions, and can be nearly an order of magnitude smaller than those based on the same assumptions generated in [35].…”
Section: Our Contributionsmentioning
confidence: 98%
“…We use our modified version of Reverie to implement post-quantum ring signatures. Our ring signatures, based on the postquantum signatures presented in [15,34,35], are the smallest known post-quantum ring signatures from symmetric key assumptions, and can be nearly an order of magnitude smaller than those based on the same assumptions generated in [35].…”
Section: Our Contributionsmentioning
confidence: 98%
“…Katz, Kolesnikov, and Wang [KKW18] extended the paradigm to MPCitH-PP and corresponding version, Picnic2, was added during Round 2. Kales and Zaverucha [KZ20] further optimized Picnic2 from various implementation aspects and accordingly proposed Picnic3. Although our masked implementation focuses on Picnic3, which is instantiated with KKW and the LowMC circuit [ARS + 15], our generic approach in Section 4 also applies to BBQ (KKW instantiated with the AES circuit) [dDOS19] and Baum and Nof's variant of KKW (instantiated over an arithmetic circuit for proving SIS instances) [BN20].…”
Section: Related Workmentioning
confidence: 99%
“…MPC in the preprocessing model. Following [GMO16, CDG + 17], Katz, Kolesnikov, and Wang [KKW18] showed that a particular communication-efficient MPC protocol in the preprocessing model is well suited to MPCitH proofs, and variants of their protocol appear in subsequent work [BN20,Beu20,dDOS19,KZ20]. The core idea of MPC in the preprocessing model is to split the protocol Π C into an offline phase Π off C and an online phase Π on C .…”
Section: Mpc-in-the-head With Preprocessingmentioning
confidence: 99%
See 2 more Smart Citations